Detection of cryptic species of Rugopharynx (Nematoda: Strongylida) from the stomachs of Australian macropodid marsupials. Issue 2 (August 2016) - Chilton, Neil B.; Huby-Chilton, Florence; Koehler, Anson V.; Gasser, Robin B.; Beveridge, Ian
Abstract: Sequences of the internal transcribed spacers of nuclear ribosomal DNA (ITS-1 and ITS-2) were determined for species of the genus Rugopharynx and Rugonema labiatum, nematodes from the stomachs of macropodid marsupials. Phylogenetic analyses of the aligned sequence data were conducted. The relationships provided molecular support for all species currently recognised, some of which are based on minor morphological differences and on multilocus enzyme electrophoretic data, but also indicated that additional, cryptic species exist within the genus. In addition, the genus Rugonema is placed as a synonym of Rugopharynx, its sole species becoming Rugopharynx labiatum n. comb. The molecular data provided some insights into the evolution of complex buccal capsule morphologies within the genus, but there was no evidence of co-evolution between the macropodid hosts and their parasites. Graphical abstract: Highlights: There was evidence of cryptic species within the nematode genus Rugopharynx . Molecular data provided insights into the evolution of complex buccal capsule morphologies. There was no evidence of coevolution between macropodid hosts and their parasites.